Teach now! physical education becoming a great PE teacher - Burton, Daniel 1986- (Routledge, Taylor & Francis Group, 2018)
"This book guides you through all the different aspects of Physical Education teaching. It examines the nature and purpose of physical education highlighting the need for a balanced curriculum that includes gymnastics, dance, swimming, athletics and outdoor and adventurous activities. Planning, assessment and differentiation are discussed in detail alongside carefully chosen examples to demonstrate good practice. There is also a strong focus on inclusion to ensure that all your students are able to make progress and achieve. With a wealth of ready-to-use activities and techniques, this is your essential guide as you start your exciting career as an outstanding Physical Education teacher"--